Corporate Renaming as a Determinant of Financial Statement Fraud: An F-Score Model Approach - Farandy, Rangga Danang; Ratmono, Dwi (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the effect of company name changes on the likelihood of financial statement fraud, as measured by the Dechow F-Score. The study sample consists of 239 observational data from companies listed on the Indonesia Stock Exchange, analyzed using logistic regression. The results show that the variable of company name changes does not have a significant effect on the likelihood of financial statement fraud. This finding suggests that company name changes are not a determining factor in detecting financial statement fraud. Instead, fundamental factors such as leverage and corporate governance play a more dominant role in influencing the likelihood of financial statement fraud.